الرواية العربية المعاصرة بين رهان التجريب واغتراب القيم - بوقرورة، عمر (كلية الدراسات الاسلامية والعربية, 2017)
This study is based on the debate between Contemporary Arabic Novel¬ist experimentation supported by overtaking and separation, and the qualita¬tive method, which continuously tends to be distinguished by consistency supported by the national peculiarities in form and content. This topic is gov¬erned by such special artistic establishment, which controversially interferes with other narratives with elements and foundations moving m a circle com¬posed of extreme formalism and obstruction and calling for keeping away from reading the text with epistemological dimensions within a cognitive, qualitative and cultural framework The topic is governed by cognitive, artis¬tic and methodological questions such as: Does experimentation represent an artistic and cognitive function at the time the Arab writer realizes that the writing with the regional, national and social spirit is of no use? Is the Arab scholar completely able, from the ele¬ments and structures of the positive experimentation that generate the artistic strength supported by the cognitive depth, to interact with the national and social values? Alternatively, do we consider experimentation not more than something marginal in the light of the artistic movement characterized by the western scholar? Is experimental writing, stemming from the Arab authors and their special identity, subject to the nation's patterns or is it a metaphorical and artistic industry? This topic might also be an observation of the concept of values when we confirm th3t the qualitative formalism does not lie in the concept and means in its simplest implications - the presence of function that the texts carry with its social and cultural context. However, the problem lies in the qualita¬tive presence associated with novelistic experimentation and interacts with it, which constitute the core of this paper.
الموضوع أساسه الجدل القائم بين التجريب الروائي العربي المعاصر المؤيد بالتجاوز والقطيعة، وبين القيمي الذي يجنح باستمرار نحو الثابت المؤيد بالخصوصيات الوطنية شكلا ومضمونا. والموضوع محكوم بذلك التأسيس الفني الخاص الذي يتداخل جدلا مع السرديات الموسومة بالتجريب تلك السرديات التي تتحرك أسسها وعناصرها الفنية في دائرة قوامها الشكلانية الموغلة في الشكل المسرفة في التجريد، الداعية إلى الابتعاد عن قراءة النص بأبعاد ابستيمولوجية ذات سند معرفي وقيمي وحضاري خاص الموضوع محكوم بالأسئلة المعرفية والفنية والمنهجية التي تتأسس بها إشكالية الموضوع ومنها: هل التجريب دال فني ومعرفي في زمن أدرك المبدع العربي أن الكتابة بالجملة الوطنية وجملة الأمة وجملة القيمة وجملة المجتمع. لم تعد تنفع؟ وهل المبدع العربي متمكن غاية التمكن من عناصر التجريب وبنياتها بصيغتها الإيجابية التي تعمل على حضور العمق الفني المؤيد بالعمق المعرفي الذي يجعل المبدع يتجاوز ويتفاعل مع قضايا وموضوعات وقيم الأمة والمجتمع؟ أم أن التجريب لا يعدو أن يكون هامشيا في ظل حركة فنية صيغتها الانبهار بالأخر الغربي، وهل الإقبال على الكتابة التجريبية نابع من ذات المؤلفين العرب ومن هويتهم الخاصة الخاضعة لصيغ الأمة، أم أن التجريب صناعة فنية استعارية؟ وفي الموضوع رصد لمفهوم القيمة حيث أكدنا أن إشكالية القيمة لا تكمن في مفهومها الذي يعني –في أبسط مدلولاته –حضور الوظيفة التي تحملها النصوص ضمن سياقاتها: الاجتماعية والحضارية. لكن المشكلة تكمن في حضور القيمي متجاورا مع التجريب الروائي ومتفاعلا معه، هذا هو مطمح الموضوع.
Keywords: الأدب العربي -- الرواية العربية -- التجريب الروائي -- السرد الروائي -- النقد الأدبي